Regulation, risk and safety of Faecal Microbiota Transplant. Issue 3 (September 2020) - Merrick, Blair; Allen, Liz; Masirah M Zain, Nur; Forbes, Ben; Shawcross, Debbie L.; Goldenberg, Simon D.
Summary: From its origins as a left-field, experimental, and even "maverick" intervention, faecal microbiota transplantation (FMT) is now a well-recognised, accepted, and potentially life-saving therapeutic strategy, for the management of recurrent Clostridiodes difficile infection (rCDI). It is being investigated as a treatment for a growing number of diseases including hepatic encephalopathy and eradication of antimicrobial resistant organisms, and the list of indications will likely expand in the future. There is no universally accepted definition of what FMT is, and its mechanism of action remains incompletely understood; this has likely contributed to the breadth of approaches to regulation depending on interpretation. In the UK FMT is considered a medicinal product, in North America, a biological product, whereas in parts of Europe, it is considered a human cell/tissue product. Regulation seeks to improve quality and safety, however, lack of standardisation creates confusion, and overly restrictive regulation may hamper widespread access and discourage research using FMT. FMT is generally considered safe, especially if rigorous donor screening and testing is conducted. Most short-term risks are associated with the delivery method (e.g. colonoscopy). Longer term risks are less well described but longitudinal follow-up of treated cohorts is in place to assess for this, and no signal towards harm has been found to date. Rarely it has been associated with adverse outcomes including the transmission of antibiotic resistant bacteria, and even death. It is vital patients undergoing FMT are well informed to the currently appreciated risks and benefits before proceeding.